ANALISIS KEMAMPUAN LITERASI DIGITAL SISWA KELAS IV SD NEGERI 99 PALEMBANG - Ummi Yanti; Ramanata Disurya; Tanzimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the digital literacy skills of fourth-grade students at SD Negeri 99 Palembang. The background of this research is based on the importance of digital literacy as an essential 21st-century skill that supports students in acquiring, processing, and using digital information wisely and responsibly. Digital literacy encompasses not only technical proficiency in using digital tools but also critical thinking, creativity, and collaboration skills. This research employs a descriptive qualitative approach, using questionnaires, interviews, and documentation as data collection techniques. The subjects of the study were 22 fourth-grade students and one homeroom teacher. The results indicate that students’ digital literacy abilities fall into the “good” category. Students demonstrated adequate abilities in accessing and utilizing information, but challenges remain in evaluating and responding critically to digital content. Therefore, teachers and schools play a crucial role in enhancing students’ understanding through contextual learning activities and the integration of information technology into the curriculum. This research is expected to provide valuable contributions to primary education by offering insights into the development of adaptive teaching strategies aligned with technological advancements and the competency demands of the future.